ATRAKSI WISATA BUDAYA DALAM MENINGKATKAN KUNJUNGAN WISATAWAN DI DESA TELUK MERANTI KECAMATAN TELUK MERANTI KABUPATEN PELALAWAN PROVINSI RIAU - Telsya Aprilia Kartika; Syofia Achnes; Siti Sofro Sidiq (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
Teluk Meranti village is a tourist destination mainstay in Pelalawan have other destination than the waves of Bono. Culture in Teluk Meranti village like Lukah Gila dance, Bono dance, martial arts, Balimau baths, and also play of Gasing can be a means to increase the tourist visit.The method used in this research is descriptive research method. Descriptive research is a research that aims to uncover the facts, the real conditions and the phenomena. Related to this research is how to manage the business culture of Teluk Meranti Village to increase the tourist visit. Therefore, the author will develop concepts, data collect, and other facts that occured in the research areas. Techniques of data collects used were in depth interview and observation, and the techniques of data analysis is used descriptive qualitative of data analysis techniques by Miles and Huberman, that is data collect, data reductions, data presentation and conclusion.The result of this research indicate that the culture of Teluk Meranti village made in an activity and event that is packaged nicely that will make attract tourist to visit the Teluk Meranti village. Events are held such as performing arts of Balimau baths, performing arts of Tirta Bono, the fishing contest, and sale of handicrafts produced by the local community. To increase the tourist visit hace faced some obstacles such as distances from the provincial capital, roads access are not good, and the other supporting facilities are inadequate.Keywords: Cultural of Tourism Attraction, Tourist, and Increase The Visits